2002
DOI: 10.1007/s00425-001-0723-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of BRH1 , a brassinosteroid-responsive RING-H2 gene from Arabidopsis thaliana

Abstract: Although many important aspects of plant development are controlled by brassinosteroids (BRs), the early molecular events of their hormonal action are largely unknown. Using a differential-display RT-PCR screen designed to detect early response transcripts, those regulated by BR treatment in the absence of de novo protein synthesis, we identified an Arabidopsis thaliana (L.) Heynh. gene (designated BRH1) that encodes a novel RING finger protein. As deduced from a complete cDNA clone, the 170-amino-acid sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 40 publications
(35 reference statements)
1
41
0
1
Order By: Relevance
“…Consistent with this, expression of BRASSINOSTEROID-RESPONSIVE RING-H2 1 (BRH1, At3g61460), whose transcript is downregulated by brassinolide (Molnar et al, 2002), was also downregulated at 6 h after cold stress. We noticed that the expression of many genes with auxinrelated roles was affected by cold stress.…”
Section: Cold Regulation Of Genes Related To Plant Hormone Biosynthessupporting
confidence: 56%
“…Consistent with this, expression of BRASSINOSTEROID-RESPONSIVE RING-H2 1 (BRH1, At3g61460), whose transcript is downregulated by brassinolide (Molnar et al, 2002), was also downregulated at 6 h after cold stress. We noticed that the expression of many genes with auxinrelated roles was affected by cold stress.…”
Section: Cold Regulation Of Genes Related To Plant Hormone Biosynthessupporting
confidence: 56%
“…For example, the RING-finger-type E3 ligases ATL2 and ATL6 were rapidly induced in Arabidopsis plants treated with chitin elicitor [39,40]. Similarly, other members of RING-type E3 ligases such as EL5 from rice and BRH1 from Arabidopsis were also induced after elicitor treatment [41,42]. The upregulation of these genes in plants suggested that they might be involved in the response to biotic stresses.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…Based on the presence of either a Cys or His residue in metal ligand position 5, RING finger domains were basically subdivided into the RING-HC (C3HC4) and RING-H2 (C3H2C3) types (Freemont 1993(Freemont , 2000Lovering et al 1993). Recently, many RING-type proteins have been implicated in various biological processes, including photomorphogenesis (COP1 and CIP8) , auxin signaling (SINAT5) (Xie et al 2002), defense signaling (ATL2) (Serrano and Guzman 2004), brassinosteroid response (BRH1) (Molnar et al 2002), seed development (RIE1) (Xu and Li 2003), adaptation to limited nitrogen (NLA) (Peng et al 2007), cold response (HOS1) (Dong et al 2006), ABA signaling (Zhang et al 2005), drought response (DRIP) (Qin et al 2008), drought stress (Rma1H1) (Lee et al 2009), and sugar response (SIS3) (Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%